2016
DOI: 10.1021/acsami.6b11556
|View full text |Cite
|
Sign up to set email alerts
|

Mix and Match: Coassembly of Amphiphilic Dendrimers and Phospholipids Creates Robust, Modular, and Controllable Interfaces

Abstract: Self-assembly of supramolecular structures has become an attractive means to create new biologically inspired materials and interfaces. We report the first robust hybrid bilayer systems readily coassembled from amphiphilic dendrimers and a naturally occurring phospholipid. Both concentration and generation of the dendrimers have direct impacts on the biophysical properties of the coassemblies. Raising the dendrimer concentration increases the hybrid bilayer stability, while changes in the generation and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Besides block copolymers, another type of synthetic polymer (dendrimer) was employed to form lipid-dendrimer co-assembly structures on solid supports. [145] The hybrid dendrimer/POPC vesicles were exposed to the hydrophilic substrates and incubated in an aqueous environment to allow them to form a well-defined supported bilayer. The fluidity and stability of the membrane could be modulated by controlling the generation (the number of repeated branching cycles) and concentration of the dendrimer.…”
Section: Lipid-polymer Hybrid Membranesmentioning
confidence: 99%
“…Besides block copolymers, another type of synthetic polymer (dendrimer) was employed to form lipid-dendrimer co-assembly structures on solid supports. [145] The hybrid dendrimer/POPC vesicles were exposed to the hydrophilic substrates and incubated in an aqueous environment to allow them to form a well-defined supported bilayer. The fluidity and stability of the membrane could be modulated by controlling the generation (the number of repeated branching cycles) and concentration of the dendrimer.…”
Section: Lipid-polymer Hybrid Membranesmentioning
confidence: 99%
“…155,156 There are many ways to construct supported lipid bilayers, 156 including vesicle fusion over a hydrated surface 44,157 or attachment to an underlying surface chemistry, 158 which allows for surface-based analyses, such as SPR, to be conducted. 76,156 Cheng and co-workers developed a benchtop method for creating nanoscale layers of glass on gold SPR substrates via a layer-by-layer deposition and calcination (LbL/calcination) approach, which produced hydrophilic surfaces that were capable of promoting vesicle fusion toward a fluid supported lipid bilayer on an SPR chip. 159161 These nanoglassified gold sensor surfaces were used in the analysis of membrane bound proteins by SPR 157 and SPRi, 162 with Hinman et al recently utilizing the methods to study the formation of hybrid bilayer interfaces consisting of phosphocholine and synthetic amphiphilic dendrimers.…”
Section: Interface Designmentioning
confidence: 99%
“…159161 These nanoglassified gold sensor surfaces were used in the analysis of membrane bound proteins by SPR 157 and SPRi, 162 with Hinman et al recently utilizing the methods to study the formation of hybrid bilayer interfaces consisting of phosphocholine and synthetic amphiphilic dendrimers. 76 Supported lipid bilayers on nanoglassified SPR chips have been extensively applied for the investigation of water-soluble deep cavitands, which self-incorporate into the bilayer, forming a pocket capable of hosting a wide variety of proteins and functionalized molecules. 114,163165 Perez et al demonstrated the use of these cavitands embedded within a supported lipid membrane for site-specific polymer growth at this biomimetic interface, enabling the attachment of nonadherent cells and proteins.…”
Section: Interface Designmentioning
confidence: 99%
“…The dendritic building blocks that are highly branched, compact, and globular are unlikely to form entanglements, allowing for facile control over morphologies compared to the linear block copolymers. [29,30] Moreover, multiple terminal groups of the dendrimers can be functionalized to control surface or interfacial properties and incorporate additional biological functionalities including targeting moieties. [27,31] Overall, amphiphilic dendrimers serve as attractive building blocks for the supramolecular construction of nanostructured materials with desirable properties.…”
Section: Introductionmentioning
confidence: 99%